Double-Sided Metasurfaces for Dual-Band Mid-Wave and Long-Wave Infrared Reflectors - Yeong Hwan Ko; Robert Magnusson (Photonics)
We present an innovative method for dual-band mid-wave infrared (MWIR) and long-wave infrared (LWIR) reflectors. By using double-sided metasurfaces, two high reflection bands can be generated with a single device. As individual guided-mode resonance (GMR) reflectors are combined with interlayer (or substrate) on the top and bottom sides, we achieved high reflection in the MWIR and LWIR bands simultaneously. Each GMR reflector was optimized as a germanium (Ge) grating structure on a potassium bromide (KBr) substrate. In our analysis, it was found that the transparency of the interlayer is critical to produce the dual-band reflection. The simulation results on the Ge/KBr/Ge double-sided metasurfaces demonstrated wideband reflection from ~3.3 to 4.8 μm and ~8.8 to 11 μm. Additionally, the device exhibited favorable angular tolerance. The work contributes to developing capability of metasurface technologies in various application fields.